Obesity and underweight among Brazilian elderly: the Bambuí Health and Aging Study Obesidade e baixo peso entre idosos brasileiros: Projeto Bambuí - Sandhi M. Barreto; Valéria M. A. Passos; Maria Fernanda F. Lima-Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
The coexistence of obesity (body mass index, BMI > or = 30kg/m²) and underweight (BMI <= 20kg/m²) and related factors were investigated among all residents aged 60+ years in Bambuí, Minas Gerais State, using multinomial logistic regression. 1,451 (85.5%) of the town's elderly participated. Mean BMI was 25.0 (SD = 4.9kg/m²) and was higher for women and decreased with age. Prevalence of obesity was 12.5% and was positively associated with female gender, family income, hypertension, and diabetes and inversely related to physical activity. Underweight affected 14.8% of participants, increased with age, and was higher among men and low-income families. It was negatively associated with hypertension and diabetes and directly associated with Trypanosoma cruzi infection and > or = 2 hospitalizations in the previous 12 months. Both obesity and underweight were associated with increased morbidity. The association of underweight with T. cruzi infection, increased hospitalization, and low family income may reflect illness-related weight loss and social deprivation of elderly in this community. Aging in poverty may lead to an increase in nutritional deficiencies and health-related problems among the elderly. A coexistência de obesidade (Índice de Massa Corpórea: IMC > ou = 30kg/m²) e de baixo peso (IMC <=20kg/m²) e seus fatores relacionados foram investigados em 1.451 idosos, 85,5% da população com 60+ anos residente em Bambuí, Minas Gerais, utilizando-se a análise logística multinomial. O IMC (média = 25,0; DP = 4,9kg/m²) foi maior nas mulheres e diminuiu com a idade. A obesidade ocorreu em 12,5% dos idosos; foi associada positivamente ao sexo feminino, à maior renda familiar e presença de hipertensão e diabete, e inversamente à atividade física. O baixo peso ocorreu em 14,8% dos idosos, aumentou com a idade, foi maior nos homens e nas famílias com menor renda, esteve inversamente associado à presença de hipertensão e de hiperglicemia e diretamente associado à infecção por Tripanossoma cruzi e duas ou mais internações no último ano. A obesidade e o baixo peso foram ambos associados a uma maior morbidade. A associação do baixo peso com a infecção por T. cruzi, maior hospitalização e menor renda pode estar refletindo a perda de peso secundária a doenças ou à privação social do idoso nesta comunidade. Envelhecer na pobreza pode aumentar as deficiências nutricionais e os problemas de saúde entre idosos.